Narratives of Place, Culture and Identity Second-Generation Greek-Americans Return 'Home' - Christou, Anastasia (IMISCoe Dissertations, 2006)
Christou explores the phenomenon of 'return migration' in Greece through the settlement and identification processes of second-generation Greek-American returning migrants. She examines the meanings attached to the experience of return migration. The concepts of 'home' and 'belonging' figure prominently in the return migratory project which entails relocation and displacement as well as adjustment and alienation of bodies and selves. Furthermore, Christou considers the multiple interactions (social, cultural, political) between the place of origin and the place of destination; network ties; historical and global forces in the shaping of return migrant behaviour; and expressions of identity. The human geography of return migration extends beyond geographic movement into a diasporic journey involving (re)constructions of homeness and belongingness in the ancestral homeland.